Pengaruh Diferensiasi Produk Dan Harga Terhadap Keputusan Pembelian Konsumen Produk Smartphone Samsung - Didi Gunawan; Viniyati Maftuchach (Prisani Cendekia, 2022)
The purpose of this study was to analyze the effect of product differentiation and price on purchasing decisions for Samsung smartphones, a case study of Samsung smartphone consumers in the South Jakarta area. This study used purposive sampling with 100 respondents, namely consumers who buy and use Samsung smartphone products. The data processed in this study using multiple linear regression analysis. Based on the results, the regression equation is obtained: 0.929 + 1.189 X1 + 0.491 X2 + e, based on statistical data analysis, the indicators in this study are valid and the variables are reliable. In the classical assumption test, multicollinearity and heteroscedasticity did not occur, and the data were normally distributed. The findings of this study indicate that: (1) product differentiation has a significant positive effect on purchasing decisions, (2) price has a positive effect on purchasing decisions. Based on the simultaneous test, it is proven that product differentiation and price variables have a significant effect on purchasing decisions.